Influence of aerification technique on recuperative potential of warm season turfgrasses - MALLESHAIAH, SHARATH KUMAR; MURUGAIAH, JAWAHARLAL; GOVINDASWAMY, VIVEK; M, GANGA; C, SURAKSHITHA N (The Indian Journal of Agricultural Sciences, 2018)
Soil compaction is the foremost adverse effect of traffic stress that interferes with turf shoot and root growth, and sequentially reduce the performance and quality of turf. Most of turfgrass soil cultivation research was emphasized on water infiltration and thatch responses to different cultivation methods. Lesser emphasis towards details of soil, recuperative potential and rooting responses of turfgrasses led to lesser success in eradicating compaction stress in turfgrass systems. This study evaluated effects of aerification on soil physical properties, growth and recuperative potential of warm season turfgrasses; Axonopus compressus, Zoysia matrella and Paspalum vaginatum. Aerificationby means of hollow tine, solid tine and water injection has found to relieve the turf soil compaction and help turfgrasses to recover from the traffic stress by regaining their growth under improved soil condition. WI evolved as best aerification technique for quick relief from soil compaction, while hollow tine aerification is a long-term relief technique to improve turf quality and turf cover by reducing the thatch and bulk density. Paspalum vaginatum exhibited good recuperative potential compared to Axonopus compressus and Zoysia matrella to recover from the traffic stress.Further, study unravels the importance of aerification techniques in turfgrass systems to rectify soil compaction to achieve a healthy and quality turf.